Mutations of phenylalanine-193 in the putative substrate access channel alter the substrate specificity of cytochrome P450(cam) - Stevenson, J; Jones, J; Wong, L (2000)
The Phe-193 residue on the surface of cytochrome P450cam is part of a cluster of residues proposed to undergo dynamic fluctuations to permit the entry of substrates into the active site pocket. The role of this residue in the activity of P450cam has been investigated. The F193A, F193V, F193I, and F193L mutations were introduced into the Y96F mutant, which had been shown to oxidize a wider range of molecules at faster rates than the wild-type enzyme. The F193L mutation had very little effect, while the F193A and F193I mutations reduced the camphor oxidation rate and almost abolished the styrene and naphthalene oxidation activity of the Y96F mutant. In contrast, the high activity of the Y96F mutant for the oxidation of adamantane, hexane, and 3-methylpentane was largely retained, although the product distributions were significantly altered. This dramatic difference between the F193L and F193I mutations warrants further investigation. The turnover rates of the Y96F-F193I with all the substrates showed the same dependence on the Pd:P450cam concentration ratio as for the Y96F mutant, clearly indicating that if the F193 mutations had affected substrate access, substrate entry was still fast compared to the first electron transfer, which remained the rate-limiting step for the overall reaction. We concluded that the F193A and F193I mutations shifted the substrate specificity of P450cam by causing structural changes that were relayed from their surface position down to the vicinity of the heme. The altered substrate binding resulted in differential electron transfer kinetics between classes of compounds.